2021
DOI: 10.3390/antibiotics10060693
|View full text |Cite
|
Sign up to set email alerts
|

Elucidating the Antimycobacterial Mechanism of Action of Decoquinate Derivative RMB041 Using Metabolomics

Abstract: Tuberculosis (TB), caused by Mycobacterium tuberculosis (Mtb), still remains one of the leading causes of death from a single infectious agent worldwide. The high prevalence of this disease is mostly ascribed to the rapid development of drug resistance to the current anti-TB drugs, exacerbated by lack of patient adherence due to drug toxicity. The aforementioned highlights the urgent need for new anti-TB compounds with different antimycobacterial mechanisms of action to those currently being used. An N-alkyl q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 98 publications
4
10
0
Order By: Relevance
“…Beteck, Seldon ( 13 ) and colleagues established that decoquinate RMB041 primarily acts on the cell wall and, second, inhibits DNA synthesis. Our findings during an earlier metabolomic investigation confirmed this and also suggested that decoquinate RMB041 inhibits protein synthesis, and pathways associated with M. tuberculosis in the nonreplicating state ( 11 ). In the current study, we examined each drug target to better understand the perturbations caused by decoquinate RMB041 and explore the cellular response by which M. tuberculosis counteracts these, such as those leading to the metabolomic changes revealed in our previous investigation and will be discussed below.…”
Section: Resultssupporting
confidence: 86%
See 2 more Smart Citations
“…Beteck, Seldon ( 13 ) and colleagues established that decoquinate RMB041 primarily acts on the cell wall and, second, inhibits DNA synthesis. Our findings during an earlier metabolomic investigation confirmed this and also suggested that decoquinate RMB041 inhibits protein synthesis, and pathways associated with M. tuberculosis in the nonreplicating state ( 11 ). In the current study, we examined each drug target to better understand the perturbations caused by decoquinate RMB041 and explore the cellular response by which M. tuberculosis counteracts these, such as those leading to the metabolomic changes revealed in our previous investigation and will be discussed below.…”
Section: Resultssupporting
confidence: 86%
“…In this study, the KEGG database BRITE hierarchy files annotated 10 of the 12 targets, of which all are involved in M. tuberculosis energy metabolism, protein synthesis, fatty acid synthesis, cell wall synthesis, TCA cycle activity, and/or amino acid synthesis. All of the aforementioned pathways were found to be altered in our previous study ( 11 ), possibly indicating the imbuing of adaptions by M. tuberculosis in an attempt to counteract or adapt to the disruption of the primary drug targets identified in this study. Correlations of M. tuberculosis genes have been extensively studied and are still barely understood.…”
Section: Resultsmentioning
confidence: 48%
See 1 more Smart Citation
“…The mode-of-action of BDQ is complex and has been investigated by multiple research demonstrating that BDQ induces Mtb's glycolytic and gluconeogenic metabolic dependencies and that pyruvate phosphate dikinase (PPDK) is a vulnerable metabolic target (62). Knoll et al (63) measured metabolite markers involved in TCA cycle metabolism, cell wall and DNA synthesis with GCxGC-TOF-MS in Mtb grown with and without ciprofloxacin, (a quinolone potent against drug resistance TB) to identify mechanism of action and Mtb's adaptation to antimicrobials (63). Comparison of drug resistant and drug susceptible metabolic profiles showed proline and isoleucine levels significantly reduced in drug resistant strains (64).…”
Section: Metabolomics and Isotopic Tracing Studiesmentioning
confidence: 99%
“…Knoll et al. ( 63 ) measured metabolite markers involved in TCA cycle metabolism, cell wall and DNA synthesis with GCxGC-TOF-MS in Mtb grown with and without ciprofloxacin, (a quinolone potent against drug resistance TB) to identify mechanism of action and Mtb’s adaptation to antimicrobials ( 63 ). Comparison of drug resistant and drug susceptible metabolic profiles showed proline and isoleucine levels significantly reduced in drug resistant strains ( 64 ).…”
Section: Metabolomics and Isotopic Tracing Studiesmentioning
confidence: 99%